(untitled) (Superficies y Vacío, 2014)
We describe a methodology to explore optimal conditions to excite surface modes in a glass-metamaterial-vacuum system (Kretschmann configuration) using both P and S polarized light. We calculate the electromagnetic dispersion relation of a metamaterial surface by solving Maxwell equations for both polarizations with appropriate boundary conditions. The dispersion relations define the frequency domain of the surface mode existence for the surface modes (with S polarization) and surface plasmons (with P polarization). In this work we report reflectivity spectra calculations, the numerical simulation of the attenuated total reflectivity technique and the electric field variations within the layer system.